Sistem Pendeteksi Kerusakan Sepeda Motor Listrik Menggunakan Fuzzy Inference System Tsukamoto - Wahyu Setyo Nurgoho (Journal of Information System and Artificial Intelligence, 2025)
With the development of technology today, there are more and more users of electric motorcycles because electric motorcycles are a cheap, affordable and environmentally friendly means of transportation. The number of electric motorcycle users is not proportional to the level of understanding of the damage and the symptoms of the damage. To overcome this, this research creates a system that can help detect damage to electric motorcycles based on the answers to symptoms experienced by customers at the Bogi Power workshop. With this system the repair process becomes fast and efficient. This study uses 21 questions with answer choices (Yes, Sometimes, No) which are assigned a value to determine the weight. In order to make the right decisions in this research, the Tsukamoto Fuzzy Inference System method is used with the rules that have been used then look for the zscore and conclusions about the damage to the electric motorcycle. Keywords : Electric Motorcycle, Fuzzy Inference System Tsukamoto